Optimize and Purification of Keratinase Produced from Local Aspergillus Terreus A13 Isolate Using A Feather as Substrate - Al-Sa’ady, Ali J. R. (Iraqi Journal of Science, 2023)
Keratin is a fibrous, insoluble structural protein that is highly cross-linked with hydrophobic, hydrogen, and disulfide bonds. Keratinases are enzymes that belong to the category of serine hydrolases that are capable of breaking down keratin. The results of the determination of the better fermentation system showed that the production of keratinase from local A.terreus A13 isolate by submerged fermentation (SmF) system was the best system to give the highest specific activity (113.4 U/mg) of keratinase compared with solid-state fermentation (SSF). The optimum conditions for keratinase production by SmF, were determined via cultivation conditions, including carbon source, nitrogen source, temperature, pH of the medium, and time of incubation were optimized to enhance the production of total keratinase production in a culture of A.terreus A13 with incubator shaker. The highest product of total keratinase was achieved in feather broth with 2 % sucrose, and 0.5 % soya bean, with a pH of 5.5 at 28 °C for 8 days. Separation and purification of keratinase from a local isolate of A.terreus A13 was done by precipitating with 0-75 % saturated ammonium sulfate, then by ion-exchange chromatography on DEAE-Cellulose column and sephadex G-150 gel. Partially purified keratinase gave an activity of 5.1 U/ml, protein concentration of 0.004 mg/ml, and specific activity of 1275 U/mg with purification fold of 4.96 and 49 % as yield. The aim of the present study was to optimize the production of keratinase from A. terreus A13, cultivated using optimum conditions, and its use for the biodegradation of feathers.